1988
DOI: 10.1128/mcb.8.8.3406
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a high-mobility-group-like DNA-binding protein that stimulates rRNA synthesis in vitro.

Abstract: A 16,000-dalton, high-mobility-group-like (HMG-like) DNA-binding protein, referred to as p16, has been purified to homogeneity from Novikoff hepatoma ascites cells. p16 binds specifically to a portion of the 5' flanking region of the rat rRNA gene (-620 to -417), which is part of the upstream activator sequence identified previously (B. G. Cassidy, H.-F. Yang-Yen, and L. I. Rothblum, Mol. Cell. Biol. 6:2766-2773, 1986). p16 also binds to a segment of the external transcribed spacer (+352 to +545). In vitro rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…It has been implicated in metaphase chromatin condensation (33), heterochromatin nucleosome phasing (53), nuclear matrix-DNA interactions (11), 3'-end processing of genes (42,49), and the formation of active initiation complexes (61,65). HMG-I is preferentially expressed at high levels in undifferentiated, neoplastically transformed, and rapidly proliferating cells (5,14,17,18,22,23,33,60); it is predicted to undergo a wide variety of posttranslational modifications (14), some of which are expected to alter its affinity for DNA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been implicated in metaphase chromatin condensation (33), heterochromatin nucleosome phasing (53), nuclear matrix-DNA interactions (11), 3'-end processing of genes (42,49), and the formation of active initiation complexes (61,65). HMG-I is preferentially expressed at high levels in undifferentiated, neoplastically transformed, and rapidly proliferating cells (5,14,17,18,22,23,33,60); it is predicted to undergo a wide variety of posttranslational modifications (14), some of which are expected to alter its affinity for DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the suggestion that they could be chromosomal structural proteins [ 131. However, recently it has been shown that HMGI proteins bind specifically to the AT-rich octamer sequence associated with a number of promoters and also to AT-rich regulatory elements of the ribosomal genes [15,16]. The finding that they can activate transcription in vitro [16] and that they have an acidic Cterminal region which is phosphorylated suggests that they …”
mentioning
confidence: 99%
“…Initiation at the ribosomal gene promoter can be stimulated by many different sequence elements operating via several distinct mechanisms. Stimulation can result not only from enhancers, but also from terminators (11,25,26,36), spacer promoters (10), and high-mobility-group-like protein binding sites (58). We would like to see the term enhancer reserved for those in vivo stimulatory elements which are analogous to the Xenopus and mouse enhancers and which match the criteria listed at the beginning of this discussion.…”
mentioning
confidence: 99%